L’affannosa ricerca per una diagnosi “utile”: tra criteri soggettivi ed evidenze oggettive - Pappagallo, Elena (Il sogno della farfalla, 2021)
The psychiatric and even more the psychotherapeutic diagnosis is still nowadays a highly debated concept which lacks a clear definition. The different theoretical framework references do not agree on a shared etiopathogenetic mechanism responsible for mental illnesses onset. Many psychiatric and psychological health care workers report the need to revise the current diagnostic manuals which, in order to favor a more operational approach, often set apart from the clinical reality. Scientific research claims a method of knowledge able to maintain its scientific nature without overestimating the importance of objectivity. Subjectivity cannot be sacrificed in order to reach an objective diagnosis. In contrast, the psychotherapeutic relational dynamics and the patient’s unconscious reality such as dreams are fundamental for a correct and deep comprehension of mental pathology. Massimo Fagioli’s Theory of Birth represents a theoretical framework able to connect the patient’s unconscious dimension to the different clinical category manifestly expressed.